2020
DOI: 10.1093/ptj/pzaa220
|View full text |Cite
|
Sign up to set email alerts
|

The Journey of Recovery: Caregivers’ Perspectives From a Hip Fracture Telerehabilitation Clinical Trial

Abstract: Objective To explore family caregivers’ perspectives of the recovery process of older adults with hip fracture, and describe experiences from caregivers who (i) used the online intervention or (ii) received home-based care provided by the Andalusian Public Health Care System. Methods This was an exploratory secondary study with informal family caregivers who had an older adult family member with hip fracture enrolled in a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Caregiver involvement is a positive predictive factor on patients' recovery [39]: We acknowledge that it also increases the demands on caregivers, as highlighted previously [40]. Nevertheless, to our knowledge, this is the first tele-rehabilitation program for older adults with hip fracture that gives an active role to caregivers who considered the program as an opportunity to increase their knowledge for patients management at home and enhance their functional recovery [41].…”
Section: Discussionmentioning
confidence: 77%
“…Caregiver involvement is a positive predictive factor on patients' recovery [39]: We acknowledge that it also increases the demands on caregivers, as highlighted previously [40]. Nevertheless, to our knowledge, this is the first tele-rehabilitation program for older adults with hip fracture that gives an active role to caregivers who considered the program as an opportunity to increase their knowledge for patients management at home and enhance their functional recovery [41].…”
Section: Discussionmentioning
confidence: 77%
“…Other studies have also shown that support from caregivers is crucial. [38][39][40] The results of this study will inform further development of MyPath to Home, 24 a web-based application to support older adults and their caregivers as they manage their personalized needs during their transition from the hospital, to rehabilitation, to home. Specifically, the barriers and enablers analysis will inform the intervention strategy.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, family caregivers have been confirmed to be an essential component of recovery after hip fracture by providing emotional and physical support. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, family caregivers have been confirmed to be an essential component of recovery after hip fracture by providing emotional and physical support. 38 However, several limitations should be acknowledged. First, like many other studies in this field, 15 marital status was assessed at the time of inclusion, thus change in marital status, such as the duration of widowhood and remarriage during the follow-up was not accounted for.…”
Section: Discussionmentioning
confidence: 99%